THE QUESTION OF THE ESSENCE AND CLASSIFICATION OF MILITARY- POLITICAL CONFLICTS (Bulletin of criminological association of Ukraine, 2023)
It is proven that a military-political conflict is a clash between two or more military-political forces or groups, caused by real or artificially created political, social, ideological contradictions, which manifests itself in the conduct of open hostilities, political pressure, informational and psychological influence etc. It is emphasized that transnational business, which plays a key role in modern military and political conflicts, needs a scientific understanding from the point of view of determining the limits of the influence of such business, including the potentially possible influence on the processes of state formation and international politics. It is noted that not only real contradictions cause individual military and political conflicts. It is also worth being aware of the so-called artificial, imposed contradictions that underlie the phenomenon of resentment, based on complex and multifaceted mechanisms of formation of hatred for a certain object among the population.
Keywords: conflict; military conflict; war; postmodern; disinformation; classification; international humanitarian law